Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage